Revisiting stock market development and growth analysis in ECOWAS: a disaggregated analysis of institutional quality as mediating variable - Richard Eshun; George Tweneboah (Cogent Social Sciences, 2024)
This study assessed whether the relationship between stock market development and economic growth in the Economic Community of West African States (ECOWAS) is conditioned by institutional quality. Empirical estimations to substantiate the mediating role of disaggregated institutional quality variables in the stock market development and economic growth relationships are performed using the Hansen threshold regression method and the study period is from 2000 to 2020. The findings revealed that good institutional structures help stock market development to have a greater positive influence on growth in the region. When institutional quality are disaggregated into its various constituents, the study results suggest that when government effectiveness is the threshold variable, stock market development has a positive and significant relationship with growth below the threshold, whereas higher regulatory control has a negative effect on how stock market development influences growth. This finding suggests that excessive government interference hinders the stock markets to have greater influence on growth. Further, the study results suggest that when rule of law, and political stability are above the estimated threshold, stock market development has a positive effect on growth whereas control of corruption, and voice and accountability negatively affect how stock market development influences growth when it is below the estimated threshold level. The findings of the study suggest that policies towards improving corruption control, voice and accountability, rule of law, and an optimum level of regulatory control, such as promoting democratic principles, instituting punitive measures to clamp down corruption, pragmatic measures to entrench rule of law can help stock market development to have a greater positive influence on growth in the ECOWAS region. ECOWAS member states are therefore encouraged to ensure various institutions are adequately resourced to enable the region to achieve the growth-enhancing effect of stock market development.